FOCAL DEPENDENCE, LOGICAL PRIORITY AND THE UNITY OF ARISTOTLE’S METAPHYSICS (Revista Kriterion, 2021)
A long-standing problem in Aristotelian scholarship concerns the question of how to reconcile Aristotle’s twofold description of metaphysics as ontology (the universal science of being qua being) and theology (the science of the changeless and separate substance). An important attempt to answer this question (advanced first by G. Patzig) consists in saying that the changelessand separate substance is focally prior to (or the focal meaning of) substance and therefore to being in general (since substance is focally prior to being in general). This article aims to refute this kind of approach to the problem of the unity of Aristotle’s metaphysics by arguing that (i) relations of focal meaning entail the logical (definitional) priority of the prior items over the dependent items standing in such relations; (ii) the changeless and separate substance is not logically prior to the other types of substances distinguished by Aristotle; and, therefore, (iii) the changeless and separate substance is not focally prior to (the focal meaning of) substance.